Implementation of Fuzzy Logic to Determine the Doneness of Beef Steak - Sista Naelly Adzimi; Robby Priaji Sakti; Aldiyansyah; Muhammad Ifan Al Aziz; Muhammad Fakhri Alauddin; Jimmy Mohamad Alpino Anak Gumay; Sesar Husen Santosa; Muhammad Danang Mukti Darmawan; Nanda Octavia (Journal of Applied Science, Technology & Humanities | JASTH, 2024)
This study aims to implement fuzzy logic in determining the doneness level of beef steak based on the inputs of roasting time and roasting temperature. The output of the developed system is in the form of maturity levels in the categories of "rare", "medium rare", "medium", "medium well", and "well done". Data for this study were obtained through interviews with experienced beef steak sellers. This research method includes direct calculations as well as the use of MATLAB software to develop fuzzy logic systems. The results of the interview analysis are used as a basis for the formation of fuzzy rules for determining the degree of doneness of steaks. The results showed that in the example case with a roasting temperature of 300°C and a roasting time of 10 minutes, the resulting output value was 70, which placed the doneness of the steak in the "medium well" position. These results have been verified both through direct calculations and the use of MATLAB software. The study concluded that the implementation of fuzzy logic can help in determining the doneness level of beef steak, based on temperature variations and roasting time.